Managing female foreign domestic workers in Singapore: Economic pragmatism, coercive legal regulation, or human rights - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2010)
Singapore's immigration discourse is deeply influenced by its need to “right-size” its population. As a society that has and remains in need of immigration, contemporary immigration and globalization have rigorously challenged the conventional thinking and understanding of citizenship, as well as notions of who belongs and who does not. Nevertheless, international marriages and pervasive in-and out-migration for purposes of employment, study, and family, conspire to make more pronounced the decoupling of citizenship and residence in Singapore. This transnational dimension sits uncomfortably with the policy makers' desire for, and the imperatives of, state sovereignty, control, and jurisdiction.Although one quarter of people living in Singapore are foreigners, concerns of human rights and justice are largely peripheral, if not absent from the immigration discourse. This is seen most clearly in employment issues pertaining to foreign female domestic workers (FDWs), most of who come from other parts of Southeast Asia. ‘Rights talk’ is largely absent even as activists seek to engage the key stakeholders through the subtle promotion of rights for such workers.The government, however, has resisted framing the FDW issues as one of rights but instead has focused on promotional efforts that seek to enhance the regulatory framework. This dovetails with the reality that immigration law also functions as quasi-family law in which the freedom of FDWs and other foreign menial workers to marry Singapore citizens and permanent residents are severely restricted. As such, the immigration regime's selectivity functions as a draconian gatekeeper. Justice and human rights are but tangential concerns.